Microstructure and lap shear strength of the weld interface in ultrasonic welding of Al alloy to stainless steel. (15th April 2016) - Fujii, Hiromichi T.; Goto, Yuta; Sato, Yutaka S.; Kokawa, Hiroyuki
Abstract: Dissimilar welds between Al alloy and stainless steel were produced with an ultrasonic welding technique. The weld strength increased with the welding energy. The welds produced with sufficiently high energy exhibited nugget pull-out failure of the Al alloy during the lap shear strength test. The welds with weld energies of more than 1.05 kJ fractured in the base metal and were severely deformed by the ultrasonic vibration, and recrystallization occurred around the weld interface owing to the shear deformation and heating during the ultrasonic welding. Graphical abstract: